A novel approach is proposed for obtaining exact travelling wave solutions to the space-time fractional Phi-4 equation - Ikram Ullah; Muhammad Bilal; Aditi Sharma; Hasim Khan; Shivam Bhardwaj; Sunil Kumar Sharma (AIMS Mathematics)
Complex physical occurrences currently need the use of nonlinear fractional partial differential equations. This paper provides a new approach to using the conformable derivative of Atangana to achieve exact travelling wave solutions to the space time-fractional Phi-4 problem. Our method enables a more profound comprehension of complex mathematical physics processes. We validate the solutions and demonstrate the effectiveness of our approaches in solving difficult nonlinear problems in nuclear and particle physics. Singular solutions can be retrieved by using the proposed method on nonlinear partial differential equations (NFPDEs). Our results are shown using contour and three-dimensional charts, which demonstrate various soliton formations for varying parameter values in the nonlinear zone. This study contributes to our growing knowledge of optical soliton.